Dynamic model for a novel liquid desiccant regeneration system operating in vacuum condition - Yon, Hao Ren (2020)
This paper presents the development of a dynamic model for a newly proposed Absorption-based Liquid Desiccant Regeneration (ALDR) system operating in vacuum condition which can reduce the regeneration temperature to around 20–35 °C. The dynamic model is developed based on the internal and external enthalpy balances and mass balances in the components and it accounts for the dynamic behavior due to the heat and mass transfer process in the components. This approach is simpler as detailed enthalpy at each state point can be avoided. The developed dynamic model is verified using the data obtained from the experimental platform constructed in the laboratory. The dynamic response of the simulation results is in good agreement with the experimental data. This model can predict the relevant parameters such as the temperature, concentration and mass flow of the desiccant solution and temperature of the heating and cooling sources when a step change of inlet water temperature is applied to system. The developed model will be useful for the elaboration of control system in the future.